Proceedings of the 2015 British HCI Conference 2015
DOI: 10.1145/2783446.2783605
|View full text |Cite
|
Sign up to set email alerts
|

Framing the community data system interface

Abstract: Researchers in public funded science consortia agree that making their data accessible with the community is their obligation. Those mandated to use Community Data Systems (CDSs) prefer to share data with their collaborators and funders rather than make it open access. Their rationale to choose against open sharing includes the lack of incentives and lapses of memory. Features that address these two aspects are not included in current CDS implementations. We speculate that an interface framed as a device to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As sharing of research enables accessibility and improves visibility, studies [44,51] found a clear connection between citation benefits for publications and open sharing of their experiment data. Thus, concerning the design of a community data system, Garza et al [31] found that emphasizing "the potential of data citations can affect researchers' data sharing preferences from private to more open. " And also badges have proven to encourage research sharing.…”
Section: Design For Supporting Research Practicesmentioning
confidence: 99%
“…As sharing of research enables accessibility and improves visibility, studies [44,51] found a clear connection between citation benefits for publications and open sharing of their experiment data. Thus, concerning the design of a community data system, Garza et al [31] found that emphasizing "the potential of data citations can affect researchers' data sharing preferences from private to more open. " And also badges have proven to encourage research sharing.…”
Section: Design For Supporting Research Practicesmentioning
confidence: 99%